2015
DOI: 10.1007/s00248-015-0672-x
|View full text |Cite
|
Sign up to set email alerts
|

Nicotiana Roots Recruit Rare Rhizosphere Taxa as Major Root-Inhabiting Microbes

Abstract: Root-associated microbes have a profound impact on plant health, yet little is known about the distribution of root-associated microbes among different root morphologies or between rhizosphere and root environments. We explore these issues here with two commercial varieties of burley tobacco (Nicotiana tabacum) using 16S rRNA gene amplicon sequencing from rhizosphere soil, as well as from primary, secondary, and fine roots. While rhizosphere soils exhibited a fairly rich and even distribution, root samples wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
40
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(48 citation statements)
references
References 24 publications
8
40
0
Order By: Relevance
“…Here, we report the impacts of phyllosphere–bacterial interactions on plant performance, determined here from assessments of the plant–microbe interaction across the plant life cycle. The phyllosphere supported a relatively greater abundance of beneficial rather than pathogenic bacteria under our common garden conditions that included the presence of fungus gnat herbivory ( Figures 1A,B and 4 ), which is consistent with the view that hosts recruit beneficial microbes in relatively greater numbers under stressed and normal conditions to obtain the maximum mutualistic benefits (Vorholt, 2012; Ortega et al, 2016; Saleem et al, 2016b). The Bacillus species group is ubiquitously abundant in soil and plant environments with multiple plant beneficial (anti-insect/pathogen) properties.…”
Section: Discussionsupporting
confidence: 83%
“…Here, we report the impacts of phyllosphere–bacterial interactions on plant performance, determined here from assessments of the plant–microbe interaction across the plant life cycle. The phyllosphere supported a relatively greater abundance of beneficial rather than pathogenic bacteria under our common garden conditions that included the presence of fungus gnat herbivory ( Figures 1A,B and 4 ), which is consistent with the view that hosts recruit beneficial microbes in relatively greater numbers under stressed and normal conditions to obtain the maximum mutualistic benefits (Vorholt, 2012; Ortega et al, 2016; Saleem et al, 2016b). The Bacillus species group is ubiquitously abundant in soil and plant environments with multiple plant beneficial (anti-insect/pathogen) properties.…”
Section: Discussionsupporting
confidence: 83%
“…Therefore, all of our RSA traits are based on growth in sterile media. There is no doubt that microbial communities are important for root growth (Rolli et al ., ; Saleem et al ., ). Indeed, anecdotally, we observed that plants heavily contaminated by microbial growth (and therefore not imaged for this study) had visibly different growth patterns.…”
Section: Discussionmentioning
confidence: 97%
“…The majority of such studies used fingerprinting techniques, which allowed differentiation of abundant bacteria at low phylogenetic resolution. In our study, we expanded investigation of the root bacteriome to the large bacterial diversity represented by low-abundance bacteria (Dohrmann et al, 2013; Nuccio et al, 2016; Saleem et al, 2016; Shi et al, 2016) and analyzed how this rare biosphere shapes the plant species-specific root bacteriome.…”
Section: Discussionmentioning
confidence: 99%
“…However, only few studies extended this knowledge so far to a more complete census of the plant species-specific rhizosphere bacterial community using modern next-generation amplicon sequencing approaches that target the phylogenetic breadth of most bacteria at sufficient sampling depth (Rodríguez-Echeverría et al, 2013; Rosenzweig et al, 2013; Hortal et al, 2015). Furthermore, studies on the role of low-abundance bacterial populations in shaping the plant species-specific root bacteriome are still scarce (Dohrmann et al, 2013; Nuccio et al, 2016; Saleem et al, 2016; Shi et al, 2016). …”
Section: Introductionmentioning
confidence: 99%